A new triple-mode microstrip bandpass filter using a patch-loaded cross resonator - Zhang, Runqi (2013)
A microstrip triple-mode bandpass filter using a single patch-loaded cross resonator is reported in this work. First, a square patch is added at the center of a cross resonator, which separates the resonant frequencies of the first and second modes. Then, a pair of slots is etched into the square patch, which splits the first pair of degenerate modes. By appropriately adjusting the patch size and the slot length, these three resonant modes are individually controlled. To feed the proposed resonator, two stub-loaded coupled lines are used to provide a required coupling degree and to suppress the lowest harmonic passband. Predicted results are well confirmed with the experimental ones.